Pengaruh Etos Kerja Islam Terhadap Prestasi Karyawan Pada PT. BPRS Al-Washliyah - Ayu Safrianti (-, 2021)
Ayu Safrianti, The Influence of Islamic Work Ethic on Employee Achievement at PT. BPRS Al-Washliyah The purpose of this study is to find out "How the implementation of the Islamic work ethic in improving employee performance at PT. BPRS AL-WASHLIYAH. This research is a quantitative research, while the analysis technique used is a simple linear analysis technique. The results of research and discussion on the effect of Islamic work ethic on employee performance at the Transit Syariah Hotel Medan carried out by giving a questionnaire to 20 respondents can be seen with the t-test value of 2.325 2.036 with sig 0.027Keywords: Islamic Work Ethic , Work Performance